Limning the Liminal: Irish Feminine Identity Formation in Éilís Ní Dhuibhne's Novelistic Borderland of Postmemory - Hadi Shahi Gharehaghaji (International Journal of Practical and Pedagogical Issues in English Education)
The question of Irish feminine identity has been the preoccupation of the contemporary Irish novelist Éilís Ní Dhuibhne (b. 1954). This article takes her two mnemonically significant novels, The Dancers Dancing (1999) and Fox, Swallow, Scarecrow (2007) to examine the formation of Irish feminine identity in a transition from the late twentieth century to the first decade of the twenty-first. The article argues that Ní Dhuibhne achieves a seemingly innovative approach in defining the liminal Irish feminine identity via postmemory through the employment of landscape and folklore in its relation to female corporeal politics and female identity formation in Ireland. At the same time, Ní Dhuibhne through the application of landscape and folklore as Stieglerian technics in Irish feminine identity formation achieves epiphylogenetic memory that politically subverts the rigid notions of Irish feminine identity and makes room for the emerging Irish feminine identity at the dawn of the twenty-first century.